Rates and Causes of Tailings Dam Failures. (22nd November 2022) - Stark, Timothy D.; Moya, Lucia; Lin, Jiale
Abstract : This paper analyzes two tailings dam databases and recent failures to assess the local and global failure rates of upstream, downstream, and centerline raised tailings dams. Since 2000, the failure rate for all three raising methods has decreased except in Brazil, which helps explain the recent Brazilian regulations banning upstream raising. However, the failure rates also show that the downstream and centerline raising methods of tailings dams are not immune to failure, so, if mining continues, one of these three raising methods will be used, and all have been involved in prior failures. The paper also presents data on failure mechanisms, showing that slope stability, earthquakes, and overtopping are the three primary causes of tailings dam failures. To continue decreasing the failure rate of tailings dams, the following features and practices should be used in all types of tailings dams: drainage systems, engineering analyses, instrumentation, monitoring, inspection, and qualified external peer review to further reduce the failure rates, especially in Brazil. Finally, a section containing data on release volume as a function of dam height and total storage volume is presented.